(untitled) (Medico Legal Update, 2021)
Background: Indonesia is the second largest population of pulmonary tuberculosis (TB) worldwide. Unfortunately, this condition has remained unchanged past decade. Education is essential for the formation of knowledge and perception, which is important, due to its impact on tuberculosis treatment implementation. Objective: The aim of this study is to determine the association between patient’s educational degree with knowledge and perception regarding pulmonary tuberculosis. Method: This was observational analytic study with cross-sectional design. The study was conducted on 51 patients in TB outpatient clinic from Siti Khodijah Hospital and two Primary Health Care in Sidoarjo. Using simple random sampling, a questionnaire was formed to obtain related information about the variables studied; including baseline characteristic (age, gender, education, occupation), patient’s knowledge, and perception regarding pulmonary tuberculosis. Then parameter’s of knowledge and perception were classified: good and low. Results: Using multivariate analysis of Wilcoxon test, there was a significant difference between each group of patient educational degree with knowledge regarding tuberculosis (p = 0.00) and perception regarding tuberculosis (p = 0.00). Conclusion: Different patient educational degree shows different knowledge and perception regarding Pulmonary TB. This result may indicate that the educational degree affected the patient to understand the disease. The collaborative approach needed to build proper patient’s knowledge and perception. Lack of knowledge regarding TB, may due to a deficiency in Indonesian school curriculum content. These results will inform the development of relevant education, and information system, to enhance awareness about tuberculosis in society.